Validation of International Club of Ascites subclassification of stage 1 acute kidney injury in chronic liver disease - Khatua, Chitta R; Sahu, Saroj K; Barik, Rakesh K; Pradhan, Subhasis; Panigrahi, Subhendu; Mishra, Debakanta; Singh, Shivaram P (JGH open, 2019)
Background and Aim Acute kidney injury (AKI) commonly occurs in patients with chronic liver disease (CLD). As per the International Club of Ascites, AKI is classified into three stages; stage 1 has recently been divided into subgroups 1A and 1B. We performed a prospective study to validate the association between subgrouping and outcome. Methods This study was conducted using decompensated cirrhosis (DC) patients hospitalized in the Gastroenterology ward between August 2016 and May 2018. Demographic, clinical, and laboratory parameters were compared between AKI 1A and AKI 1B patients. The duration of hospitalization and outcome were compared. Results A total of 528 subjects were enrolled; 296 (56.1%) had AKI, and of them, 61.48% (n = 182) had stage 1, 20.95% (n = 62) had stage 2, and 17.57% (n = 52) had stage 3 AKI. Of the enrolled patients, 100 (54.94%) had early (AKI 1A) and 82 (45.06%) had late stage 1 AKI (AKI 1B). Patients with AKI 1B had higher total leucocyte count, total bilirubin, serum urea, serum creatinine (SCr), model for end‐stage liver disease (MELD), MELD‐Na+, and child‐turcotte‐pugh (CTP) score and decreased serum albumin than AKI 1A. The prevalence of hepatorenal syndrome (HRS), acute on chronic liver failure (ACLF) were higher in AKI 1B patients, and they had a prolonged hospital stay compared to AKI 1A patients. Furthermore, AKI 1B patients had significantly lower survival both at 28 days and 90 days. Conclusion Our study validates the subclassification of stage 1 AKI. Patients with AKI 1B more often progress to higher AKI stages with significantly lower 28‐day and 90‐day survival rates. Results justify subclassification and suggest the need for early intervention. The small increase in SCr should be viewed with caution in AKI stage 1A. Our study validates the subclassification of stage 1 acute kidney injury (AKI). Patients with AKI 1B more often progress to higher AKI stages with significantly lower 28‐days and 90‐days survival. Results justify subclassification and suggest need for early intervention; small increase in serum creatinine should be viewed with caution in AKI 1A stage.